2016
DOI: 10.1159/000442917
|View full text |Cite
|
Sign up to set email alerts
|

Risk Genes of Inflammatory Bowel Disease in Asia: What Are the Most Important Pathways Affected?

Abstract: Genetic factors play an important role in the pathogenesis of inflammatory bowel disease (IBD), and IBD is now recognized as a complex disease that results from interplay between genetic and environment factors. To date, over 160 IBD-susceptible loci have been identified using genome-wide association studies (GWAS). The risk genes identified in these studies are involved in various pathways in innate and adaptive immune response such as innate bacterial sensing, autophagy and interleukin-23 receptor/T-helper c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Furthermore, it is noted that familial aggregation is lower among South Asian IBD patients. This contributed to the hypothesis that genetic contribution to IBD is lower among Asians compared to their Caucasian counterparts, which is refuted by some scientists[12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is noted that familial aggregation is lower among South Asian IBD patients. This contributed to the hypothesis that genetic contribution to IBD is lower among Asians compared to their Caucasian counterparts, which is refuted by some scientists[12].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, over 200 single nucleotide polymorphisms (SNPs) in several genes (such as NOD2/CARD15, NOD1/CARD4 , and ABCB1 ) are related to CD in Western populations [69]. However, due to genetic differences, some SNPs failed to show a link to CD in the Asian population [10,11]. For example, mutations within genes from the NOD2/CARD15, ATG16L1 , and IL23/Th17 signaling pathways were demonstrated to confer susceptibility to CD only in Western patients and not in Chinese and Japanese patients [1215].…”
Section: Introductionmentioning
confidence: 99%
“…We also identified 51 eQTL at 18 IBD risk loci. The association of the human leucocyte antigen (HLA) region with Asian IBD risk has been replicated in several studies and was found to make a bigger contribution to the Asian IBD than to that of Caucasians . The HLA region has extended LD, and the association of this region with IBD may be caused by a tight LD between a causal variant and a tag SNP.…”
Section: Discussionmentioning
confidence: 95%